Ecuador's first biennial transparency report and fifth national communication - Instituto Interamericano de Cooperación para la Agricultura (IICA) (2025)
To support Ecuador, prepare and submit its First Biennial Transparency Report (BTR1) and Fifth National Communication (NC5) that comply with the United Nations Framework Convention on Climate Change (UNFCCC) and Paris Agreement reporting requirements while responding to national development goals. At the national level, to allow for “built-in flexibility” if the country needs it considering its capacities and national circumstances, priorities, and needs while bridging gaps identified.